2020
DOI: 10.2217/imt-2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Plus Ipilimumab for Soft Tissue Sarcoma: A Single Institution Retrospective Review

Abstract: Aim: To analyze the efficacy of checkpoint inhibitors in soft tissue sarcoma. Materials & methods: We retrospectively reviewed patients with advanced soft tissue sarcoma treated with ipilimumab and nivolumab. All patients who received at least one cycle were included. Results: One patient had a complete response and five had a partial response, for an objective response rate of 15%. Clinical benefit rate was 34% with a median duration of 12.0 months (range: 4.5 to 28.9+ months [mo]). Median overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In the first-line setting, a retrospective study of nivolumab with or without ipilimumab in PDL1-positive STS found a significant benefit for the combination group in terms of ORR (13% vs. 7%), median PFS (4.1 m vs. 2.2 m) and median OS (12.2 m vs. 9.2 m) [ 142 ]. A similar ORR (15%) was observed in a retrospective study with ipilimumab plus nivolumab for advanced STS [ 143 ]. The combination ipilimumab plus nivolumab is also being evaluated by a phase II trial in patients with pre-treated classic KS (NCT03219671), with a promising ORR of 50% in an interim analysis [ 144 ].…”
Section: Immunotherapy For Sarcoma: Clinical Resultssupporting
confidence: 78%
“…In the first-line setting, a retrospective study of nivolumab with or without ipilimumab in PDL1-positive STS found a significant benefit for the combination group in terms of ORR (13% vs. 7%), median PFS (4.1 m vs. 2.2 m) and median OS (12.2 m vs. 9.2 m) [ 142 ]. A similar ORR (15%) was observed in a retrospective study with ipilimumab plus nivolumab for advanced STS [ 143 ]. The combination ipilimumab plus nivolumab is also being evaluated by a phase II trial in patients with pre-treated classic KS (NCT03219671), with a promising ORR of 50% in an interim analysis [ 144 ].…”
Section: Immunotherapy For Sarcoma: Clinical Resultssupporting
confidence: 78%
“…Responses were recorded in 8/25 (32%) and 9/20 (45%) of patients with UPS and LMS, respectively. Furthermore, the use of combination ipilimumab-nivolumab to treat heterogeneous STS cohorts in prospective series from China and Stanford University was associated with levels of anti-tumour activity similar to that seen in the ALLIANCE study, with responses seen in cases of UPS, LMS, and DDLPS [23,24]. Also notable are the reported efficacy results from a randomised phase II trial where patients with localised, resectable UPS or DDLPS were treated with nivolumab with or without ipilimumab for a month prior to surgery [25].…”
Section: Clinical Trials Of Cpis In Mixed Sts Cohortsmentioning
confidence: 57%
“…Out of T cell immunotherapies, CPIs are the most widely used agents. However, both nivolumab and ipilimumab in monotherapies showed only limited efficacy [71,123]. The undifferentiated pleomorphic sarcoma histology is associated with better response and CPIs combination therapies, such as nivolumab plus pembrolizumab, significantly increase the response rates in STSs patients.…”
Section: Discussionmentioning
confidence: 99%